2022
DOI: 10.1038/s41598-022-16900-1
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive inotropic score as a predictor of long-term mortality in patients after off-pump coronary artery bypass grafting

Abstract: Increased vasoactive-inotropic score (VIS) is a reliable predictor of mortality and morbidity after cardiac surgery. Here, we retrospectively evaluated the association between VIS and adverse outcomes in adult patients after off-pump coronary artery bypass grafting (OPCAB). We included 2149 patients who underwent OPCAB. The maximal VIS was calculated for the initial 48 postoperative hours using standard formulae. The primary outcome was 1-year death. The composite adverse outcome was death, resuscitation or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…In addition, if added to the cardioplegic solution, esmolol may provide additional protection by reducing myocardial activity [19][20][21] . Over the years, meta-analyses of randomized trials [23,[30][31][32][33][34] have been performed, which have confirmed that if esmolol is administered during a cardiac surgery, the rate of perioperative myocardial ischemia, occurrence of arrhythmias after CABG, as well as a reduced need for inotropic support in the postoperative period is reduced.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, if added to the cardioplegic solution, esmolol may provide additional protection by reducing myocardial activity [19][20][21] . Over the years, meta-analyses of randomized trials [23,[30][31][32][33][34] have been performed, which have confirmed that if esmolol is administered during a cardiac surgery, the rate of perioperative myocardial ischemia, occurrence of arrhythmias after CABG, as well as a reduced need for inotropic support in the postoperative period is reduced.…”
Section: Discussionmentioning
confidence: 94%
“…Vasoactive inotropic score (VIS) was calculated for each patient according to the following formula: (Dobutamine dose (µg/kg/min) + Dopamine dose (µg/kg/min) + Epinephrine dose (µg/kg/min x100) + Norepinephrine (µg/kg/min x100) ++ Enoximone dose (µg/kg/ min) during the operation itself, as well as in the postoperative period [31,32,33,34] .…”
Section: According To the Protocol For The Inclusion Of Esmololmentioning
confidence: 99%
“…The inclusion criteria of the studies included either acute coronary syndrome (ACS), mix of ACS and chronic coronary syndrome (CCS), or MI. Majority studies included patients undergoing PCI while two studies ( 16 , 26 ) included only CABG patients. In one study ( 29 ) the patients were managed by either PCI or CABG while in another ( 30 ) PCI or medical management was undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…PNI was initially described to check the nutritional status of gastrointestinal surgery, but over the years it has been recognized as an important prognostic factor in several cancers (11)(12)(13). Over the past years, many studies have also used PNI to predict prognosis of CAD patients but with inconsistent results (14)(15)(16)(17)(18). However, no systematic review has been attempted to summarize the available evidence.…”
mentioning
confidence: 99%
“…In our study, M-VVR was confirmed to be positively associated with the poor prognosis of patients undergoing CABG. Previous studies have reported the positive association between VIS and poor prognosis in cardiac surgery [ 9 , 27 ]. Kwon et al manifested that increased postoperative VIS was independently correlated with the risk of 1-year mortality after CABG in adults [ 27 ].…”
Section: Discussionmentioning
confidence: 99%